Analysis of Constraints and Opportunities for the Development of Smallholder Coconut Oil Processing Industry in Micro Enterprises Konawe Islands Regency - Baka, La Rianda; Alwi, La Ode; Herdhiansyah, Dhian; Fyka, Samsul Alam; Hisein, Waode Siti Anima (Department of Agribusiness, Halu Oleo University, 2020)
It is based on the fact that small-scale coconut oil processing in micro-scale businesses is facing serious threats and competition with palm oil produced by large and medium-sized entrepreneurs, resulting in a downturn in business as well as weakening the motivation of coconut farmers to process coconut production into coconut oil. As a result, coconut farmers in their daily lives actually buy palm oil processed by large and medium entrepreneurs, while their businesses are getting worse. In line with this, through this research, an analysis of the obstacles and opportunities for the development of the people's coconut oil processing industry was carried out. The purpose of this study was to analyze the barriers to developing the people's coconut oil processing industry on a micro-scale business and to analyze the opportunities for developing the people's coconut oil processing industry on a micro-scale business. The research method is through a Focus Group Discussion (FGD) to identify obstacles and opportunities for developing the coconut oil processing industry, followed by Analysis Hierarchy Process (AHP) to determine priority problems and priority opportunities that should be carried out by multi-stakeholders for the development of the coconut oil processing industry. The results showed that the priority obstacles to the development of the coconut oil processing industry in micro-scale businesses in Konawe Islands Regency were product marketing problems, financial capital, and business funding problems, production equipment problems, skilled labor issues, raw material problems, micro-business protection policy issues, business organization, and management problems, as well as problems in the use of information technology and innovation. The priority of opportunities for the development of the micro-scale coconut oil processing industry in Konawe Kepualauan Regency is the presence of economic value by-products of coconut oil processing, namely shell charcoal, nata de coco, and coconut coir, there is a tendency for people to consume more coconut oil than consume coconut oil. Palm oil, the existence of a government program to encourage the coconut processing industry, and the nutritional value that is unique to coconut oil. Organizational and business management problems, as well as problems in the use of information technology and innovation. The priority of opportunities for the development of the micro-scale coconut oil processing industry in Konawe Kepualauan Regency is the presence of economic value by-products of coconut oil processing, namely shell charcoal, nata de coco, and coconut coir, there is a tendency for people to consume more coconut oil than consume coconut oil. Palm oil, the existence of a government program to encourage the coconut processing industry and the nutritional value that is unique to coconut oil. Organizational and business management problems, as well as problems in the use of information technology and innovation. The priority of opportunities for the development of the micro-scale coconut oil processing industry in Konawe Kepualauan Regency is the presence of economic value by-products of coconut oil processing, namely shell charcoal, nata de coco, and coconut coir, there is a tendency for people to consume more coconut oil than consume coconut oil. Palm oil, the existence of a government program to encourage the coconut processing industry and the nutritional value that is unique to coconut oil.